Pengaruh Bauran Pemasaran Terhadap Keputusan Konsumen Membeli Produk Mebel BMS Pontianak - M. Haris Hidayat; Edy Suryadi; Fenni Supriadi (Universitas Muhammadiyah Pontianak, 2018)
The purpose of this study was to determine how much influence BMS Furniture made the marketing mix on the decision of consumers to buy Pontianak BMS furniture products. The population in this study were all consumers who had purchased products in BMS Pontianak Furniture with a total of 100 respondents. Analysis techniques used were a simple linear regression analysis, correlation coefficient, determination coefficient, and model feasibility test. The results of simple linear regression analysis show that the marketing mix has a positive and significant effect on purchasing decisions. The simple linear regression equation is Y = 4,759 + 0,342 X. The result of the correlation coefficient shows the R-value of 0.278 so that it can be concluded that the marketing mix has a positive but low relationship with the consumer's decision to buy Pontianak BMS Furniture products. The result of the coefficient of determination shows the R2 value of 0.078, which means that the marketing mix influences 7.8% of consumers' decisions to buy BMS Pontianak Furniture products and the remaining 92.2% is influenced by other variables outside this research. The results of the model feasibility test show that the calculated F value is 8.234> table F 3.94, and has a significance value of 0.005 (less than 0.05), so it can be concluded that a simple linear regression model can be used to predict consumer decisions to buy BMS furniture products Pontianak which are influenced by the marketing mix.